Optimalisasi Pengelolaan Sampah dan Pembangunan Berkelanjutan di Desa Sugiale Kabupaten Bone (Studi Kasus Bank Sampah Al-Muqarrabin) - Azis, Muh. Rafli; Jamil, Muh; Kamaruddin, Citra Ayni; Irwandi (Jurnal EMT KITA, 2025)
Waste management can be considered the 'entry point' to achieving sustainable development goals, because this problem is multisectoral and affects various aspects of people's lives. Waste management through the waste bank program has become an innovative and sustainable solution for the government and society in reducing the volume of waste which continues to increase every day. This research aims to determine the effectiveness of using digital platforms on waste bank business income and the impact of waste management through the waste bank program in sustainable development efforts in Sugiale Village, Bone Regency. This research uses a qualitative descriptive research method using a policy evaluation perspective. The data used is primary data obtained through observation, interviews and documentation methods. Data were analyzed using Miles and Huberman's effectiveness analysis and interactive analysis. The results of this research show that the use of digital platforms is effective in the business income of the Al-Muqarrabin waste bank in Sugiale Village, Bone Regency. Apart from that, the Al-Muqarrabin waste bank program also has a positive impact on various aspects of life of the people of Sugiale Village, Bone Regency, such as the economic aspect by providing additional income for the community, the environmental aspect by increasing environmental cleanliness and village aesthetics, and the social aspect by increasing community awareness of the environment and also increasing community solidarity.